Role of exogenous fibrolytic enzymes in ruminant feeding - CHANDRASEKHARAIAH, M; D, PRASANNA KUMAR; SANTOSH, SUNIL SINGH; PALANIVEL, C; CHIGURUPATI, SRINU; PRASAD, C S (The Indian Journal of Animal Sciences, 2014)
The complex crop residues and straws are main feed resource available for feeding livestock in developing countries like India. These straws mainly consist of ligno-cellulose complex, which is not very easily and fully digested. Several attempts were tried to address the issue but met with varying degree of success. One of the approaches which holds promise is the use of exogenous fibrolytic enzyme in animals that are mainly fed on crop residue based diets. The major enzymes involved in cellulose hydrolysis are endocellulase (endoglucanase, endo- ß–1, 4-glucanase, carboxymethyl cellulase or ß-1, 4-glucan glucanohydrolase; E.C. 3.2.1.4), exocellulase (exoglucanase, exo-ß-1, 4-glucanase, cellulose ß-1, 4-cellobiosidase; E.C. 3.2.1.91), and ß-glucosidase (cellobiase or glucohydrolase, E.C. 3.2.1.21). Many of these enzymes are being used worldwide in numerous industrial applications such as food industry in addition to animal feed industry. Use of the exogenous enzymes in cattle improved the digestibility of feeds, growth rate and milk production although results obtained were inconsistent. This review gives an insight into various exogenous fibrolytic enzymes involved in cell wall digestion, probable mode of action, and their level of inclusion as productivity enhancer in ruminant feeding.